Solid phase crystallization of amorphous silicon at the two-dimensional limit. Issue 3 (19th December 2022) - Dhungana, Daya S.; Bonaventura, Eleonora; Martella, Christian; Grazianetti, Carlo; Molle, Alessandro
Abstract : We present a novelty in the synthesis of 2D ultrathin silicon on Ag(111) and silicene-on-Ag(111) by molecular beam epitaxy. Abstract : The epitaxy of silicene-on-Ag(111) renewed considerable interest in silicon (Si) when scaled down to the two-dimensional (2D) limit. This remains one of the most explored growth cases in the emerging 2D material fashion beyond graphene. However, out of a strict silicene framework, other allotropic forms of Si still deserve attention owing to technological purposes. Here, we present 2D Solid Phase Crystallization (SPC) of Si starting from an amorphous-Si on Ag(111) in atomic coverage to gain a crystalline-Si layer by post-growth annealing below 450 °C, namely Complementary Metal Oxide Semiconductor (CMOS) Back-End-of-Line (BEOL) thermal budget limit. Moreover, considering the benefit of the 2D-SPC scheme, we managed to write crystalline-Si pixels on the amorphous-Si matrix. Our in situ and ex situ analyses show that an in-plane interface or a lateral heterojunction between amorphous and crystalline-Si is formed. This amorphous-to-crystalline phase transformation suggests that 2D silicon may stem from an epitaxially grown layer and thermal self-organization/assembling.